Will Asia shape or shake the world economy? - George Magnus (European Centre for International Political Economy (ECIPE), 2012)
Asia's economic rise has changed the world economy - and will continue to do so in the future as well. George Magnus in his policy brief claims that no one should doubt that Asia now is part of shaping world trade, capital markets, commodities and consumer markets. But there may also be a considerable amount of shaking involved. The past four years have demonstrated that many countries in the West relied on flawed economic models. Yet it is also increasingly clear that many countries in Asia need to change economic policy - and the model for economic development - if they should continue growing at elevated levels. This is true also for China. China's growth in the future needs to be less dependent on growth in fixed capital formation and more anchored in growth in consumption and local entrepreneurship. It will take time to achieve such reforms - and they will prove politically challenging as they equally concern basic institutions. In the short term, China may be tempted to cushion negative effects from the crisis in the Eurozone by expanding credit, a counter-cyclical measure China has often used. But the economic return from that model is shrinking. Beyond China, Asia countries in general need to reform political, economic and regulatory institutions in order to maintain growth. Some of them are at risk of getting stuck in the middle-income trap. A surprisingly few number of those countries that were middle-income countries in the 1960s have now grown to become high-income countries. That should serve as a warning to those who extrapolate China's future growth on the trend in the past decades.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Wirtschaftsordnung; Entwicklung; Asien